ON PSEUDO-PARTICIPIAL IN NOMINAL GROUP - Anum Dahlia (Universitas Widyatama, 2021)
In nominal group, noun is the central word or as a modified word. It can be modified by several elements. One modification of a noun is by a noun added with –ed ending, then labelled pseudoparticipial. Pseudo-participial as modifier is not frequently used, but it exists. The objectives of this study are to identify the formation and to find out the meaning of pseudo-participial. The method used in this study is descriptive qualitative. She analyzed the data and described them based on the theories of Systemic Functional Grammar (SFG). The data were collected from Corpus of Contemporary American English (COCA). The results reveals that the formation of pseudo-participial is placed before head named as pre-head modifier, it can be preceded by its own sub-modifier, such as intensifier or adjective, and it functions as epithet in nominal group structure. Pseudo-participial means having which can be elaborated using finite clause, non-finite clause, or prepositional phrase.